Tracking Japan's development assistance for health, 2012-2016 - Shuhei Nomura; Haruka Sakamoto; Maaya Kita Sugai; Haruyo Nakamura; Keiko Maruyama-Sakurai; Sangnim Lee; Aya Ishizuka; Kenji Shibuya (BMC, 2020)
Abstract Background Development assistance for health (DAH) is one of the most important means for Japan to promote diplomacy with developing countries and contribute to the international community. This study, for the first time, estimated the gross disbursement of Japan's DAH from 2012 to 2016 and clarified its flows, including source, aid type, channel, target region, and target health focus area. Methods Data on Japan Tracker, the first data platform of Japan's DAH, were used. The DAH definition was based on the Organisation for Economic Co-operation and Development's (OECD) sector classification. Regarding core funding to non-health-specific multilateral agencies, we estimated DAH and its flows based on the OECD methodology for calculating imputed multilateral official development assistance (ODA). Results Japan's DAH was estimated at 1472.94 (2012), 823.15 (2013), 832.06 (2014), 701.98 (2015), and 894.57 million USD (2016) in constant prices of 2016. Multilateral agencies received the largest DAH share of 44.96-57.01% in these periods, followed by bilateral grants (34.59-53.08%) and bilateral loans (1.96-15.04%). Ministry of Foreign Affairs (MOFA) was the largest contributors to the DAH (76.26-82.68%), followed by Ministry of Finance (MOF) (10.86-16.25%). Japan's DAH was most heavily distributed in the African region with 41.64-53.48% share. The channel through which the most DAH went was Global Fund to Fight AIDS, Tuberculosis, and Malaria (20.04-34.89%). Between 2012 and 2016, approximately 70% was allocated to primary health care and the rest to health system strengthening. Conclusions With many major high-level health related meetings ahead, coming years will play a powerful opportunity to reevaluate DAH and shape the future of DAH for Japan. We hope that the results of this study will enhance the social debate for and contribute to the implementation of Japan's DAH with a more efficient and effective strategy.